2017
DOI: 10.5301/ejo.5001052
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive case series of 244 age-related macular degeneration patients undergoing implantation with an extended macular vision IOL

Abstract: This novel IOL appears safe in the short to medium term. Improvements in postoperative CDVA and CNVA exceed those observed with standard implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…There are a few reports on the use of dual optic system using two IOLs to create an intraocular Galilean telescopic system,13 14 and recently there has been one report on the use of wavefront-optimised IOL (iolAMD Eyemax mono) to provide enhanced quality of vision during cataract surgery in patients with AMD. However, it is unclear how the optics of this IOL works 15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few reports on the use of dual optic system using two IOLs to create an intraocular Galilean telescopic system,13 14 and recently there has been one report on the use of wavefront-optimised IOL (iolAMD Eyemax mono) to provide enhanced quality of vision during cataract surgery in patients with AMD. However, it is unclear how the optics of this IOL works 15…”
Section: Discussionmentioning
confidence: 99%
“…Although this device could be implanted through a small, self-sealing incision it had the same drawbacks of having a telescopic optics inside the eye causing severe restriction to the field of vision. Recently, there has been a report on the use of wavefront optimised IOL to provide enhanced quality of image on the macula during cataract surgery in patients with AMD 15. The Scharioth macula lens (SML) (A45 SML, Medicontur, Hungary) is a single-piece hydrophilic IOL implanted monocularly in the ciliary sulcus as a supplementary/piggyback IOL in pseudophakic eyes with AMD.…”
Section: Introductionmentioning
confidence: 99%
“…There were no intraoperative or postoperative complications related to the IOL in our series, which is a foldable lens implanted in a routine approach with a universal injector through a 2.2-mm or larger clear cornea incision [ 11 ]. Similarly, Qureshi et al [ 4 ] reported favorable safety and visual acuity improvement in a study of another injectable AMD IOL. Not only is the LENTIS® MAX LS-313 MF 80 IOL an injectable lens, but it is built on the same platform as several existing presbyopia-correcting IOLs (LENTIS® Mplus MF 20 and MF 30, LENTIS® Comfort, OSD Medical, Germany).…”
Section: Discussionmentioning
confidence: 88%
“…Vision impairment in eyes with advanced dry AMD is characterized by central scotoma that interferes with the ability to recognize faces, read, drive a car, and complete numerous other routine daily activities that are essential for independent living [3]. Although magnifying aids and vision rehabilitation techniques that train patients to utilize the intact peripheral retina can help individuals cope with their central vision loss, these strategies suffer drawbacks that make them less than ideal [4].…”
Section: Introductionmentioning
confidence: 99%
“…Data are now emerging for EyeMax Mono, a new single-piece, soft, hydrophobic, acrylic IOL that increases breadth of focus and reduces blur, thereby improving image quality across all areas of the macula and not just the foveal center. [6,7] The lens optics are wavefront-optimized to provide an enhanced quality of image to an area extending 10° from the foveal center, and laboratory simulations indicate that the lens delivers superior image quality compared with standard monofocal IOLs at 4° and 7.5° of retinal eccentricity. [6]…”
Section: Introductionmentioning
confidence: 99%